Insights into the Neotropics prior to the Great American Biotic Interchange: New evidence of mammalian predators from the Miocene of Northern Colombia - Suarez Gomez, Sandra Catalina (2016)
A new species of Sparassodonta (Mammalia, Metatheria), Lycopsis padillai, sp. Nov., is described on the basis of a partial left maxilla with M1-M4 and fragments of lacrimal and jugal. The material comes from the early to early middle Miocene Castilletes Formation, La Guajira Peninsula, Colombia. This specimen represents the northernmost record of a fossil metatherian in South America and integrates a highly diverse vertebrate association, recently discovered in the north of Colombia. The La Guajira specimen is referred to the genus Lycopsis, as supported by the results of our phylogenetic analysis. This analysis also demonstrates that species of Lycopsis (L. torresi, L. longirostrus, L. viverensis, and L. padillai) constitute a monophyletic group and are placed as the basal taxon of Borhyaenoidea. Lycopsis padillai is a large-sized sparassodont with a body mass of about 22 kg. The presence of Lycopsis from La Guajira extends the geographical distribution of the genus to the entire South America, representing the sparassodont with the widest latitudinal distribution.